Utilization of water hyacinth (Eichhornia crassipes) rejects as phosphate-rich fertilizer (2021)
Phosphorus (P) recovery from water hyacinth is one of the promising sources to recovery and recycle P to alleviate P supply shortage in the future. The result of calcination temperature during the thermal treatment of calcium (Ca) and P-rich water hyacinth is presented here. Results showed a Ca/P molar ratio of 5.07 in water hyacinth ashes and, that with the increase in calcination temperature, P and Ca are transformed into hydroxyapatite. The amount of hydroxyapatite increased until 34.0 %, while other Ca phases such as CaO, CaCO3, and Ca(OH)2 were obtained in 6.1 %, 3.9 %, and 18.0 %, respectively. The bioavailability test showed that the material produced at 700 °C (hydroxyapatite and other Ca-rich phases) could be used as a fertilizer, with P slow release in aqueous solutions, giving up 3.7 % and 29.3 % of P release in deionized water and formic acid, respectively. Besides, CaO and Ca(OH)2 are used for soil neutralization as their disposition can help the crops. © 2020 Elsevier Ltd.